HAKIKAT GLOBALISASI DAN DAMPAKNYA TERHADAP TRADISI PESANTREN - Satria, Rama; Muhammad Wardiansyah; Abdurrahmansyah; Tutut Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article aims to discuss the nature of globalization and its impact on Islamic boarding schools as traditional Islamic educational institutions in Indonesia. Islamic boarding schools as part of a global society are experiencing transformation in various aspects, including curriculum, use of information technology, and cultural exchange. In the context of globalization, Islamic boarding schools face challenges and opportunities. Curriculum modernization is also needed to prepare students to face the demands of the modern world. However, on the other hand, the influence of foreign culture and dependence on technology can also erode the traditional values ​​of Islamic boarding schools. This research method uses a qualitative approach with a type of library research because the main data source in this research is by searching journals, news, books and other relevant literature. This article presents research results that describe the adaptation of Islamic boarding schools to globalization, including efforts to integrate information technology, curriculum modernization, and international cooperation. The latest references included provide a more comprehensive understanding of the phenomenon of globalization and its impact on Islamic boarding schools in Indonesia.